2015
DOI: 10.1038/scsandc.2015.15
|View full text |Cite|
|
Sign up to set email alerts
|

Thoracic spinal cord compression by extradural tophus: a case report and review of the literature

Abstract: STUDY DESIGN: Case report and literature review. OBJECTIVES: Gouty arthritis of the spine is rare. Gout presenting as back pain and quadriplegia may be difficult to distinguish from a spinal tumor. Symptoms vary, and the diagnosis is often delayed. We report an unusual case of thoracic spinal cord compression caused by extradural tophaceous deposits whose initial diagnosis had been lymphoid malignancy. To the best of our knowledge, this is only the second report of using single-photon emission computed tomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The necropsy of that patient showed that the tophi had eroded the first cervical vertebrae causing a pathological fracture of the atlas with protrusion of the odontoid process into the foramen magnum. Since Kersley's original article, a few case reports of patients with spinal cord involvement caused by gout tophi have been published [5,6,[8][9][10][11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The necropsy of that patient showed that the tophi had eroded the first cervical vertebrae causing a pathological fracture of the atlas with protrusion of the odontoid process into the foramen magnum. Since Kersley's original article, a few case reports of patients with spinal cord involvement caused by gout tophi have been published [5,6,[8][9][10][11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…In the vertebral column, gout tophi can affect different anatomical components, such as the articular facets, the vertebral bodies, the pedicles, the laminae, and the yellow ligaments. The lateral parts of the vertebra are usually more affected than the central areas [ 13 - 15 ]. The patient here described showed facet hypertrophy at the dorsal and lumbar levels with signs of spinal cord compression.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there have been few reports concerning the use of [ 99m Tc]-methylene diphosphonate (MDP) single-photon emission computed tomography (SPECT)/CT imaging to assess spinal tophi. [3][4][5][6] Here, we discuss the usefulness of [ 99m Tc]-MDP SPECT/CT imaging in the diagnosis of gout spondylitis.…”
Section: Introductionmentioning
confidence: 99%
“…Kersley et al reported the first case of tophaceous gout of the spine in 1950 when he identified post-mortem tophaceous destruction of the upper cervical spine (5). Since then there have been multiple case reports of tophaceous gout in the cervical (6,7), thoracic (8)(9)(10) and lumbar spine (11)(12)(13)(14); with the lumbar spine being the most common site (2,3,14). There are currently only about three reports involving more than one region of the spine (1,6,15,16).…”
Section: Introductionmentioning
confidence: 99%
“…The presenting features of spinal gout include back pain (17), radiculopathy (11,12), myelopathic symptoms (10), paraparesis (8) or quadriplegia (6). In some cases, patients are asymptomatic and are not diagnosed until post-mortem (19,20).…”
Section: Introductionmentioning
confidence: 99%